New perspectives on microsoft windows vista : Comprehensive - Parsons, June Jamrich; Oja, Dan; Carey, Patrick; Carey, Joan; Ruffolo, Lisa (United States of America : Thomson / Course Technology, 2008)
Tiene un enfoque de resolución de problemas basado en casos para la enseñanza de habilidades de Microsoft Windows Vista.
Tutorial 1. Exploring the basics of microsoft windows vista Tutorial 2. Organizing your files Tutorial 3. Personalizing your windows environment Tutorial 4. Working with the internet and E-Mail Tutorial 5. Protecting your computer y otros más...
Incluye glosario
Incluye índice
Incluye bibliografía
Keywords: MICROSOFT WINDOWS (PROGRAMA PARA COMPUTADOR); SISTEMAS OPERACIONALES (COMPUTADORES)